The EIF4A3/CASC2/RORA Feedback Loop Regulates the Aggressive Phenotype in Glioblastomas - Zhao, Junshuang; Jiang, Yang; Chen, Lian; Ma, Yue; Zhang, Haiying; Zhou, Jinpeng; Li, Hao; Jing, Zhitao (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is a common and refractory subtype of high-grade glioma with a poor prognosis. The epithelial-mesenchymal transition (EMT) is an important cause of enhanced glioblastoma invasiveness and tumor recurrence. Our previous study found that retinoic acid receptor-related orphan receptor A (RORA) is a nuclear receptor and plays an important role in inhibiting proliferation and tumorigenesis of glioma. We further confirmed RORA was downregulated in GBM. Thus, we determined whether RORA was involved in the migration, invasion, and EMT of GBM. Human GBM cell lines, U87 and T98G, and patient-derived glioma stem cells (GSCs), GSC2C and GSC4D, were used for in vitro and in vivo experiments. The expressions of RORA, CASC2, and EIF4A3 in GBM cells and GSCs were detected by RT-qPCR and western blotting. The biological effects of RORA, CASC2, and EIF4A3 on GBM migration, invasion, and EMT were evaluated using the migration assay, transwell assay, immunofluorescence staining, and xenograft experiments. We found that RORA inhibited the migration, invasion, and EMT of GBM. CASC2 could bind to, maintain the stability, and promote the nuclear translocation of RORA protein. EIF4A3 could downregulate CASC2 expression via inducing its cleavage, while RORA transcriptionally inhibited EIF4A3 expression, which formed a feedback loop among EIF4A3/CASC2/RORA. Moreover, gene set enrichment analysis (GSEA) and in vitro and in vivo experiments showed RORA inhibited the aggressiveness of GBM by negatively regulating the TGF-β1/Smad signaling pathway. Therefore, The EIF4A3/CASC2/RORA feedback loop regulated TGF-β1/Smad signaling pathway might become a promising therapeutic strategy for GBM treatment.